All the World's Futures- Participating Countries and Collateral Events : 56th International Art Exhibition- La Biennale di Venezia 2015 (Venice; Marsilio Editori, 2015)
The 56th International Art Exhibition entitled All the World$1 (Bs Futures is curated by Okwui Enwezor. 44 Collateral Events, approved by the curator of the International Exhibition and promoted by non profit national and international institutions, present their exhibitions and initiatives in various locations within the city of Venice.s
English
Keywords: Biennial Collateral events catalog; N4390-5098 Visual Arts- Exhibitions; Italy